Academic journals. Part 2. Sub-genre development, functions and problems after 1989 - Monika Kubiak (Forum Bibliotek Medycznych, 2022)
This article presents the development, problems and in-depth characteristics of the academic (university) journals published in Poland after the socioeconomic transformation of 1989. It also comments on the emergence of a new term to describe university magazines, and looks at the conventions that were organ-ised for their editors (the exchange of views and experiences, and the search for new forms of expression and functions of this particular press genre), the means of financing and the problems facing these maga-zines, as well as the position of the editorial offices within the university structures. The paper closes with remarks on the journalistic and editorial workshops, and the influence of the internet and electronic forms of the magazines on the printed editions.